2005
DOI: 10.1158/1078-0432.ccr-04-1483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Panel of Tumor Markers for Molecular Detection of Circulating Cancer Cells in Women with Suspected Breast Cancer

Abstract: Purpose: We examined the feasibility of using molecular characterization of circulating tumor cells as a method for early detection of breast cancer. Research Design: Women without a prior history of cancer who had a breast abnormality detected on imaging followed by a breast biopsy were enrolled in this study. Density gradient centrifugation and immunomagnetic capture were used to enrich for epithelial cells from f20 mL of blood. Real-time reverse transcription-PCR was used to quantitate the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 50 publications
(58 reference statements)
1
44
1
5
Order By: Relevance
“…Taken together with the correlation of GABRP with the BLBC subtype, metastatic spread to the brain, overall patient survival, and the migratory ability of BLBC cells described herein, GABRP may be a viable therapeutic target for treating BLBC. Supporting this possibility, GABRP is consistently detected in circulating breast tumor cells (51)(52)(53)(54) and in lymph nodes isolated from breast cancer patients (55). Targeting GABRP should be achievable because it is a cell surface receptor subunit.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together with the correlation of GABRP with the BLBC subtype, metastatic spread to the brain, overall patient survival, and the migratory ability of BLBC cells described herein, GABRP may be a viable therapeutic target for treating BLBC. Supporting this possibility, GABRP is consistently detected in circulating breast tumor cells (51)(52)(53)(54) and in lymph nodes isolated from breast cancer patients (55). Targeting GABRP should be achievable because it is a cell surface receptor subunit.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, RT-PCR based methods have been established as an alternative to ICC. Various markers were evaluated including mammaglobin and cytokeratin 19 (CK19) [8][9][10][11][12][13]. CK19 is an intermediate filament cytokeratin and stably expressed in epithelial tissues but not in mesenchymal haemopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to several recent studies, [34][35][36] the use of a panel of molecular markers provides a more sensitive method for the detection of several human malignancies including colorectal cancer, lung cancer and breast cancer. In the present study, we demonstrated that with combination of 4 mRNA markers, expression of any 3 mRNA markers could achieve the highest diagnostic accuracy (90.3%) in discrimination between GC patients and normal persons, with sensitivity of 89.1% and specificity of 91.3%, whereas 4 detectable mRNA markers were an independently unfavorable prognostic predictor for GC patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%